2008
DOI: 10.1016/j.cma.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic model identification of uncertainties in computational models for dynamical systems and experimental validation

Abstract: We present a methodology to perform the identification and validation of complex uncertain dynamical systems using experimental data, for which uncertainties are taken into account by using the nonparametric probabilistic approach. Such a probabilistic model of uncertainties allows both model uncertainties and parameter uncertainties to be addressed by using only a small number of unknown identification parameters. Consequently, the optimization problem which has to be solved in order to identify the unknown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 56 publications
0
49
0
1
Order By: Relevance
“…This prior probability distribution is constructed by using the Maximum Entropy Principle [20] (from Information Theory [21]) for which the constraints are defined by the available information [13,14,22,15]. Since the paper [13], many works have been published in order to validate the nonparametric probabilistic approach of model uncertainties with experimental results (see for instance [23,24,25,26,27,28,15,29]), to extend the applicability of the theory to other areas [30,31,32,33,34,35,36,37,38,39,40,41], to extend the theory to new ensembles of positive-definite random matrices yielding a more flexible description of the dispersion levels [42], to apply the theory for the analysis of complex dynamical systems in the medium-frequency range, including vibroacoustic systems, [43,44,23,45,25,26,27,28,46,47,48,39], to analyze nonlinear dynamical systems (i) for local nonlinear elements [49,50,37,…”
Section: Types Of Approach For Stochastic Modeling Of Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This prior probability distribution is constructed by using the Maximum Entropy Principle [20] (from Information Theory [21]) for which the constraints are defined by the available information [13,14,22,15]. Since the paper [13], many works have been published in order to validate the nonparametric probabilistic approach of model uncertainties with experimental results (see for instance [23,24,25,26,27,28,15,29]), to extend the applicability of the theory to other areas [30,31,32,33,34,35,36,37,38,39,40,41], to extend the theory to new ensembles of positive-definite random matrices yielding a more flexible description of the dispersion levels [42], to apply the theory for the analysis of complex dynamical systems in the medium-frequency range, including vibroacoustic systems, [43,44,23,45,25,26,27,28,46,47,48,39], to analyze nonlinear dynamical systems (i) for local nonlinear elements [49,50,37,…”
Section: Types Of Approach For Stochastic Modeling Of Uncertaintiesmentioning
confidence: 99%
“…Such a prior stochastic model can then be used to study the propagation of uncertainties through the mechanical system which is analyzed. If experimental data are available for the mechanical system, then they can be used (1) to identify the parameters of the prior stochastic model [29] using, for instance, the maximum likelihood method [57,58] or (2) to construct a posterior stochastic model [12] using, for instance, the Bayesian method (see for instance [59,60,61,62,58]). …”
Section: Types Of Representation For the Stochastic Modeling Of Uncermentioning
confidence: 99%
See 1 more Smart Citation
“…There exists several methodologies adapted to the identification of stochastic computational models, see for instance [46,47,48]. In the present research, the identification procedure is achieved using the maximum likelihood method associated with a statistical reduction of the information [49]. Note that it is particularly adapted to the present case for which the random variables U obs (s i , δ) are not only dependent but also strongly correlated.…”
Section: Identification Of the Stochastic Nonlinear Static Computatiomentioning
confidence: 99%
“…Note that the likelihood function is replaced by an approximation which is constructed as the product of marginal probability density functions of each uncorrelated random variable. Although this assumption modifies the Likelihood function, it has been shown that its combination with the statistical reduction yield accurate estimations [49]. Seeking the maximum of L red (δ) for the experimental identification yields the optimal value δ opt = 0.45.…”
Section: Identification Of the Stochastic Nonlinear Static Computatiomentioning
confidence: 99%